Phenomenological model of heat transfer in hard-disk air bearing based on nonlocal behavior in air molecular gas - Poletkin, Kirill V. (2013)
In this paper, a new phenomenological model of heat transfer in hard-disk air bearing based on nonlocal behavior in air molecule is developed. Analysis of the model shows that it is a more accurate to simulate the behavior of heat transfer due to heat conduction and the viscous dissipation for Couette flow case. Since, assumption of the nonlocal behavior (in space) in air molecular, due to its scattering from the boundaries of the domain through which air flow is moved, allows us to eliminate deficiencies of continuum model, in particular, based on the temperature jump theory.